The Potential Therapeutic Targets of Anlotinib in Osteosarcoma: Characterization Based on Patient‐Derived Xenografts and Next‐Generation Sequencing - Zuoyao Long; Yajie Lu; Minghui Li; Jing Li; Guojing Chen; Fengwei Wang; Qi Wang; Liangbi Xiang; Zhen Wang (Cancer Medicine)
ABSTRACT Background The aim of this study was to analyze the potential therapeutic targets of anlotinib using the patient‐derived xenografts (PDX) and evaluate the efficacy of the combination of chemotherapy and anlotinib in osteosarcoma patients before surgery. Methods Forty‐three osteosarcoma specimens were used to establish the PDX model in mice, resulting in Twenty‐one PDX successful models. Eventually, six models were randomly selected for the pharmacodynamic experiment. The tumor‐bearing mice were randomly divided into the anlotinib (3 mg/kg) and placebo groups (n = 5 each). After treatment, the tumors were harvested and analyzed by immunohistochemistry (IHC) and western blotting. Results In PDX model establishment, the tumors from donors with relapse, metastasis or chemoresistance demonstrated higher engraftment capacity. Histology results suggested that anlotinib significantly inhibited the growth of osteosarcoma by inducing mitotic arrest, necrosis and apoptosis, and selective against tumors with high expression of VEGFR2, PDGFRβ and CD31. Based on these results, five osteosarcoma patients who had progressed during NAC were treated with the combination of anlotinib and chemotherapy before surgery, which led to tumor regression in four patients. Next‐generation sequencing showed that most patients with tumor reduction expressed medium or high levels of VEGFR2 and PDGFRβ mRNA. The toxicities were tolerable. Conclusions In conclusion, osteosarcoma with high expression of VEGFR2, PDGFRβ and CD31 is more sensitive to anlotinib. However, the potential of synergistic effect of anlotinib and chemotherapy in osteosarcoma patients needs further investigation.